Multicultural Hong Kong: alternative new media representations of ethnic minorities. (3rd April 2017) - Jackson, Liz; Nesterova, Yulia
Abstract: Racial and ethnic minorities experience misrecognition, prejudice and discimination in Hong Kong. In response to these challenges, multicultural education there aims to enable young people to recognize diversity in a more tolerant, open-minded way. Educators have been encouraged to not rely only on textbooks, but to include news and digital media in such teaching. This paper examines online media representations of diversity in Hong Kong in the context of multicultural education, focusing on Apple Daily ( AD ), a popular liberal Hong Kong news source. We analyze how AD represents ethnic minorities, contributing to the construction of a particular multicultural environment and identity among Hong Kong people. Despite its multicultural orientation, AD remains problematic as a learning tool. In relation we recommend that more alternative digital media be used to learn about diversity in Hong Kong. We give as an example the use of student self-authored digital texts during the Hong Kong Umbrella Movement, which enabled ethnic minorities to engage in performative citizenship. We identify a focus on multiple, self-authored perspectives as part of critical media literacy, which we regard as essential for young people to better understand diversity, in contrast to straightforward reliance on multicultural news sources.